Methane Reduction Potential of Brown Seaweeds and Their Influence on Nutrient Degradation and Microbiota Composition in a Rumen Simulation Technique - Künzel, Susanne; Yergaliyev, Timur; Wild, Katharina J.; Philippi, Hanna; Petursdottir, Asta H.; Gunnlaugsdottir, Helga; Reynolds, Chris K.; Humphries, David J.; Camarinha-Silva, Amélia; Rodehutscord, Markus (Frontiers in Microbiology, 2022)
This study aimed to investigate the effects of two brown Icelandic seaweed samples (Ascophyllum nodosum and Fucus vesiculosus) on in vitro methane production, nutrient degradation, and microbiota composition. A total mixed ration was incubated alone as control or together with each seaweed at two inclusion levels (2.5% and 5.0% on dry matter basis) in a long-term rumen simulation technique (Rusitec) experiment. The incubation period lasted 14 days, thereof seven days of adaptation and sampling, respectively. Methane concentration of total gas produced was decreased at 5% inclusion level of A. nodosum and F. vesiculosus by 8.9 and 3.6%, respectively (P < 0.001). Total gas production was reduced by all seaweeds with a greater reduction for the 5% seaweed inclusion level (P < 0.001). Feed nutrient degradation and the production of volatile fatty acids and ammonia in the effluent were also reduced, mostly with a bigger effect for the 5% inclusion level of both seaweeds, indicating a reduced overall fermentation (all P ≤ 0.001). Microbiota composition was analyzed by sequencing 16S rRNA amplicons from the rumen content of donor cows, fermenter liquid, and effluent on day 7 and 13, and feed residues on day 13. Relative abundances of most abundant methanogens varied between the rumen fluid used for the start of incubation and the samples taken on day 7, as well as between days 7 and 13 in fermenter liquid and effluent (P < 0.05). According to the differential abundance analysis with q2- ALDEx2, in effluent and fermenter liquid samples archaeal and bacterial amplicon sequence variants were separated into two groups (P < 0.05). One was more abundant in samples taken from the treatment without seaweed supplementation. The other one prevailed in seaweed supplemented treatments. This group also showed a dose-dependent response to seaweed inclusion, with a greater number of differentially abundant members between 5% inclusion level and unsupplemented samples than between 2.5% inclusion level and TMR. Although supplementation of both seaweeds at 5% inclusion level decreased methane concentration in total gas, due to the high iodine content in the seaweeds tested, the application in practical feeding should be made with caution.